Water Storage Discharge and Refilling in the Main Stems of Canopy Tree Species Investigated Using Frequency Domain Reflectometry and Point Electronic Dendrometers - Carrasco, L. O. (2013)
Water storage in the trunks of large trees plays an important role in whole-plant water balance on both daily and seasonal bases. To investigate the dynamics of water storage and usage in tree trunks, diurnal changes in volumetric water content (VWC) of the sapwood and tree radius including the bark were monitored continuously using frequency domain moisture sensors and electronic point dendrometers in 10 canopy tree species of a subtropical seasonal forest in northern Argentina. In addition, species-specific water storage capacitance of the active xylem was assessed using pressure volume relationships determined with a psychometric method. In nearly all the species, trunk VWC and radius length decreased during the day when the air saturation deficit increased, suggesting that the trunk water storage was drawn by canopy transpiration, while the increase of VWC during the night suggests stem water storage recharge. Species with higher water storage capacitance exhibited lower wood density and higher average VWC, suggesting the influence of wood structural properties on its water storage function.